Potential Assessment and Development Strategy of Ecotourism In Bokor Village of Meranti Archipelago Regency of Riau Province - Mulyadi, Aras; Siregar, Yusni Ikhwan; ', Arfitrah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was aimed to: 1) assess the potential and condition of mangrove ecosystems in Bokor Village to be developed into ecotourism destination, 2) knowing the level of community participations and perceptions, 3) knowing the effort and perceptions of stakeholders concerning to development ecotourism in Bokor Village, and 4) developing a strategy for ecotourism in Bokor Village. The methods used in this study were observation, survey and interviews.The results showed that the mangrove forest in the Bokor Village had good density with very dense with a density of 2955.55 Ind/ha and there were 13 species of mangrove flora. The average value of the category of community participation showed 0.41, thus community participation in the development of ecotourism in the Bokor Village was relatively low. The average value of the category community perceptions was 3.32, it means the level of community perceptions of ecotourism development was classified as supporting category. Furthermore, the results showed that the stakeholders related provide a very strong support for the development of ecotourism in the Bokor Village.Based on the result of SWOT analysis, the development strategy in the Bokor Village was by applying an aggressive strategy (Growth Oriented Strategy) or also known as S-O Strategy (Strength-Opportunities). This consisted of making the general management plan and conservation site plan for the development of ecotourism, building and adding the quality of products/services ecotourism (High Quality), improving access to a wider market and establishing cooperation with universities or research institutions in the field of research and conservation.Keywords: Bokor Village, Ecotourism, Participations, Perceptions